PENGARUH DANA ALOKASI UMUM (DAU), DANA ALOKASI KHUSUS (DAK), DAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP BELANJA LANGSUNG DI PROVINSI JAWA TENGAH TAHUN 2013-2017 - Fadhila Yuniar Rachmawati; Haryanto Haryanto (Diponegoro Journal of Accounting, 2019)
The results of this study indicate that the General Allocation Fund (DAU) and Regional Original Revenue (PAD) have a positive and significant effect, while the Special Allocation Fund (DAK) has a non-significant result of Direct Expenditure. The aim of this study is to find out which income can be extracted in order to increase public welfare and regions with direct expenditure.